2016
DOI: 10.1111/cea.12797
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis identifies potential diagnostic biomarkers for aspirin‐exacerbated respiratory disease

Abstract: SummaryBackground To date, there has been no reliable in vitro test to diagnose aspirin-exacerbated respiratory disease (AERD). Objective To investigate potential diagnostic biomarkers for AERD using metabolomic analysis. Methods An untargeted profile of serum from asthmatics in the first cohort (group 1) comprising 45 AERD, 44 patients with aspirin-tolerant asthma (ATA), and 28 normal controls was developed using the ultra-high-performance liquid chromatography (UHPLC)/QToF MS system. Metabolites that discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…The study subjects were divided into group 1 (asthmatics who experienced AE during the study period) and group 2 (those who did not). The LTE 4 and PGF 2α levels were quantified as previously reported 8. In brief, Mass Hunter Quantitative Analysis B.07.00 (Agilent Technologies, Santa Clara, CA, USA) was used to quantify the LTE 4 and PGF 2 levels in plasma samples.…”
Section: Methodsmentioning
confidence: 99%
“…The study subjects were divided into group 1 (asthmatics who experienced AE during the study period) and group 2 (those who did not). The LTE 4 and PGF 2α levels were quantified as previously reported 8. In brief, Mass Hunter Quantitative Analysis B.07.00 (Agilent Technologies, Santa Clara, CA, USA) was used to quantify the LTE 4 and PGF 2 levels in plasma samples.…”
Section: Methodsmentioning
confidence: 99%
“…The serum and urinary levels of S1P and five eicosanoid metabolites, LTE4, prostaglandin F2 α (PGF2 α ), thromboxane B2 (TXB2), 15-hydroxyeicosatetraenoic acid (15-HETE), and eoxin C4, were determined using the Agilent 6530 quadrupole time-of-flight (Q-TOF) mass spectrometer. The device settings have been described in detail in a previous study [18]. …”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon is present in both random urine and 24 h urine; recent studies on 24 h urine have reported an area under the curve (AUC) of 0.87 [ 35 ]. In addition, it was confirmed that the metabolites of urinary LTE4 were significantly different in NERD and ATA, even in studies that used metabolomics [ 37 ]. Urinary LTE4 can be used not only to distinguish between NERD and ATA but also to indicate the prognosis and treatment response.…”
Section: Biomarkers Of Nerdmentioning
confidence: 96%